Audio augmented objects and the audio augmented reality experience - Cliffe, Laurence (2022)
This thesis explores the characteristics, experiential qualities and functional attributes of audio augmented objects within the context of museums and the home. Within these contexts, audio augmented objects are realised by attaching binaurally rendered and spatially positioned virtual audio content to real-world objects, museum artefacts, physical locations, architectural features, fixtures and fittings.